A new neolignan and antioxidant phenols from Nectandra grandiflora - Ribeiro, Alan B. [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Yoshida, Massayoshi; Santos, Leonardo S.; Eberlin, Marcos N.; Silva, Dulce Helena Siqueira [UNESP] (FapUNIFESP (SciELO), 2005)
The EtOH crude extract from the leaves of Nectandra grandiflora collected in the Atlantic Forest, Brazil, showed antioxidant activity towards β-carotene in a TLC assay. The bioassay-guided fractionation led to the isolation of protocatechuic acid and two flavonol glycosides: afzelin and quercetrin, which showed free radical scavenging activity towards DPPH (ΔA 32, 16 and 73% at 50 μmol L-1) and were compared to commercial antioxidants rutin (81% at 50 μmol L-1) and BHT (9% at 50 μmol L-1), used as standard compounds. Additionally, three inactive neolignans, including the new bicycle[3.2.1]octane neolignan 2′-oxo-piperol B were obtained and characterized by spectrometric methods. ©2005 Sociedade Brasileira de Química.
Keywords: Antioxidant; Flavonoid; Lauraceae; Nectandra grandiflora; Neolignan; Radical scavenging activity